2021
DOI: 10.5114/ada.2021.107932
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum omentin-1 and apelin concentrations in patients with hidradenitis suppurativa

Abstract: Introduction Recent studies suggest a role of adipokines in the pathogenesis of hidradenitis suppurativa (HS). Omentin-1 and apelin are two recently identified adipokines that have been involved in the regulation of metabolic and inflammatory responses. Aim To investigate serum omentin-1 and apelin levels in patients with HS and to assess their associations with metabolic parameters, disease severity and HS risk. Material and methods This cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There was no correlation between disease severity and ghrelin. Omentin-1 was also found to be elevated in HS patients compared to healthy controls after adjustment for BMI, age, and sex [ 58 ]. Omentin-1 is an adipocytokine expressed in visceral fat.…”
Section: Resultsmentioning
confidence: 99%
“…There was no correlation between disease severity and ghrelin. Omentin-1 was also found to be elevated in HS patients compared to healthy controls after adjustment for BMI, age, and sex [ 58 ]. Omentin-1 is an adipocytokine expressed in visceral fat.…”
Section: Resultsmentioning
confidence: 99%
“…Adipokine levels such as elevated omentin-1 (a recently identified adipokine) were found to be altered in patients with HS compared with controls. 48 Results from clinical studies and meta-analyses of patients with depression also have demonstrated that adipokines are dysregulated in this population, 49,50 which may be another potential genetic link between depression and HS.…”
Section: Commentmentioning
confidence: 86%
“…Surprisingly, disease severity did not have a significant effect on bone turnover markers, BMD, or TBS. In this regard, previous studies have also failed to demonstrate an association between HS severity and serum adipokine levels disturbances, suggesting that even mild disease is sufficient to trigger systemic inflammation and impair bone homeostasis ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several adipokines are dysregulated in HS, even after adjustment for BMI. This imbalance could influence bone metabolism, although the role of these adipokines in patients with HS has not been assessed ( 47 49 ). Surprisingly, disease severity did not have a significant effect on bone turnover markers, BMD, or TBS.…”
Section: Discussionmentioning
confidence: 99%